PENGARUH MODEL BLENDED LEARNING BERBANTUAN GAME EDUKASI ONLINE TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS 3 SEKOLAH DASAR - Wibowo, Andi; Maulidah, Vera Fajariyatul (Universitas Islam Raden Rahmat Malang, 2023)
This research is motivated by the low learning outcomes of students in thematic learning for grade 3 SDN 02 Bringin Wajak. There are several factors that researchers encountered in the learning process that affect student learning outcomes such as: 1) The use of models that are still not varied, 2) Less effective learning so that the goals are not achieved optimally. Therefore, this study aims to determine whether the effect of blended learning model assisted by online educational games on cognitive learning outcomes of 3rd grade elementary school students. The research method uses a quasi-experimental data collection technique through observation, by giving questionnaires, filling out test questions and collecting documentation. This study assesses the cognitive aspect using an instrument in the form of a test (pre-test and post-test). The population in this study were students in grades 3A and 3 B at SDN 02 Bringin Wajak in the 2022 academic year with a total of 45 students. The data obtained were then calculated using the normality test, homogeneity test and T-test with the help of IBM Statistical v.23. The calculation obtained that the t-count value is 0.00 and the t-table is 0.206 so that the t-count table means that Ho is rejected at a significant level of a = 0.05. So it can be concluded that Ha states that there is an influence between blended learning learning models on cognitive learning outcomes. This shows a significant effect on students' cognitive learning outcomes.